2020
DOI: 10.1212/nxi.0000000000000860
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the NEOS score in Chinese patients with anti-NMDAR encephalitis

Abstract: ObjectiveThe performance of anti-NMDAR Encephalitis One-Year Functional Status (NEOS) in predicting the 1-year functional status in Chinese patients with anti-NMDAR encephalitis is unknown.MethodsWe recruited patients with anti-NMDAR encephalitis from the Multicenter and Prospective Clinical Registry Study of Anti-NMDAR Encephalitis in Beijing Area. Patients were followed up for 1 year. We defined the poor functional status as a modified Rankin Scale score of more than 2 and good functional status as a modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…However, even being not statistically significant, we found that treatment delay could be an important 1-year outcome predicting factor. This result is consistent with those reported in 2 large series of NMDAR ( 8 , 10 ). Other studies also found that an early immunosuppressive treatment could prevent long-term cognitive deficits in anti-LGI-1 LE ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, even being not statistically significant, we found that treatment delay could be an important 1-year outcome predicting factor. This result is consistent with those reported in 2 large series of NMDAR ( 8 , 10 ). Other studies also found that an early immunosuppressive treatment could prevent long-term cognitive deficits in anti-LGI-1 LE ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…Early diagnosis is important and can be made prior to the Ab-test results as well as in the absence of positive autoimmune antibody detection ( 9 ). Specific tools have been developed to predict the 1-year outcome of patients presenting with NMDAR encephalitis ( 8 , 10 ), which allow specific therapeutic management with induction or escalation strategies. There is no validated tool to predict outcome in other Ab-mediated AE.…”
Section: Introductionmentioning
confidence: 99%
“…In the multivariate regression model assessing all clinical data obtained within 4 weeks of starting treatment, the predictive value of the NEOS score was validated in this prospective cohort, which provided another Class III evidence of using the NEOS score as a tool to predict 1-year functional status in patients with anti-NMDAR encephalitis 3 , 5 . It is of interest to notice that patients in the low-FT3 subgroup had higher NEOS scores, which might provide a clue to predict the NEOS score in the early stage of the disease.…”
Section: Discussionmentioning
confidence: 91%
“…Each of them was assigned 1 point to create the NEOS score, which was strongly associated with the probability of poor functional status at 1 year 4 . It seemed to be a reliable tool to predict the 1-year outcome and was recently validated by another team in Chinese population 5 . However, some of the variables may not be obtained until 4 weeks of starting treatment, which in some extent limit its use in the early stage of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, 17% of the patients had relapses during the first 12 months, which is higher than previous studies (e.g., 12% over the first 2 years), and the frequency of tumors was lower (19.5%) than that previously reported (38%). In a separate study from China, Dr. Peng and colleagues 27 studied 111 patients with anti-NMDAR encephalitis and validated the anti-NMDAR encephalitis 1-year functional status (NEOS) score as a reliable predictor of poor functional status at 1-year follow-up.…”
mentioning
confidence: 99%